Front Cover: Nickel‐Catalyzed 1, 1‐Difluoroethylation of (Hetero)aryl Halides with 1, 1‐Difluoroethyl Chloride (CH3CF2Cl) (Asian J. Org. Chem. 3/2020). Issue 3 (17th March 2020) - Liu, Jianchang; Zhang, Jida; Li, Xiangye; Wu, Chaolin; Liu, Hefu; Liu, Hui; Sun, Fenggang; Li, Yueyun; Liu, Yuying; Li, Xinjin
Abstract : 1, 1‐Difluoroethylated aromatic compounds are of increasing importance in drug design because the 1, 1‐difluoroethyl group (CF2 CH3 ) can function as a bioisostere of the methoxy group. Compounds such as those in the accompanying graphic may help combat viruses such as the Coronavirus, which has been affecting Wuhan and the entire world. Herein, we disclose a nickel‐catalyzed 1, 1‐difluoroethylation of (hetero)aryl halides with CH3 CF2 Cl, an inexpensive and available raw material. The reaction exhibits good functional‐group tolerance and is regarded as a practical method for synthesis of (1, 1‐difluoroethyl)arenes. Initial mechanism studies show that a 1, 1‐difluoroethyl radical is involved in the current reaction. More information can be found in the Communication by Xinjin Li et al. on page 391 in Issue 3, 2020 (DOI: 10.1002/ajoc.202000004 ).